Associations of DNMT3B −149C>T and −2437T>A polymorphisms and lung cancer risk in Chinese population. Issue 1 (December 2016) - Gao, Min; He, Daqiang; Meng, Fanji; Li, Jianing; Shen, Yan
Abstract Background DNMT3B polymorphisms are associated with the susceptibility of lung cancer.DNMT3B −2437T>A is a novel polymorphism, and its influence on the risk of lung cancer in Chinese was investigated in this study. In addition, effect ofDNMT3B −149C>T polymorphism on lung cancer was also explored. Methods Genotyping in subjects were performed by PCR-RFLP. Haplotype frequencies were estimated by estimating haplotype software. Adjusted odds ratios (ORs) with 95% confidence intervals (CIs) were calculated by unconditional logistic regression analysis. Results Neither of the two polymorphisms was correlated with lung cancer (−149C>T: CT+TT vs CC: OR = 0.78, 95%CI, 0.57 to 1.05, P  = 0.361; −2437T>A: AT+AA vs TT: OR = 0.99, 95%CI, 0.74 to 1.33, P  = 0.168). In stratification analysis, T-allele carrier genotype of −149C>T polymorphism resulted in a reduced lung cancer risk at stage II, compared with CC (OR = 0.46, 95%CI, 0.28 to 0.77, P  = 0.023). In haplotype analysis, when −149C/−2437T was used as reference, the other combined genotypes of the two polymorphisms had no significant effect on lung cancer risk (P  > 0.05). Conclusions The twoDNMT3B polymorphisms are not correlated with lung cancer risk among Chinese population nor the haplotype of them.